The Influence of Translation Techniques on the Accuracy of Interpretation of Little Women by Louisa May Alcott - Suryadi, Fidela Shaumi; Azzakhro, Devika Fatimah; Fauzan, Dheriyan; Ardiansya, Erlan Aditya (Program Studi Pendidikan Bahasa Inggris, 2024)
This study analyzes the influence of translation techniques on the accuracy of the interpretation of Louisa May Alcott's novel